(untitled) (Advancements in Homeopathic Research, 2025)
Introduction : cough is one of the most frequently reported medical symptoms in clinical pratice. Its features duration and serveity depand on the etiogly . the symptoms are greatly affcted by enviromental fectors also. kofeez cough syrap a hemopathic formulation by medisynth , is wedly prescribed for all types of coughs across age of groups since decrades . the present survey is aimed to assess doctors preception , prescriprtion pattern , and crinical expresions with kofiz couph syrap across india